A doping and defect co-modified crystalline g-C3N4 material and its preparation method and application

The crystalline g-C3N4 material with sodium/lithium doping and defect co-modified crystalline g-C3N4 material was prepared by co-modified doping and defect, which solved the problem of insufficient performance of existing graphite carbon nitride materials in catalytic H2O2 generation, and achieved efficient and stable photocatalytic performance, which was suitable for industrial applications.

CN119158612BActive Publication Date: 2025-03-07CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661983.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing graphite carbon nitride (g-C3N4) materials have problems such as insufficient light absorption capacity, poor carrier mobility, low O2 adsorption, low selectivity of dual electron oxygen reduction (2e-ORR) and insufficient stability in catalytic H2O2 generation.

Method used

By co-modifying the doping and defects, using urea as a raw material, combined with eutectic salts of lithium chloride and sodium chloride for heat treatment, a crystalline g-C3N4 material doping and defects was prepared. This method not only improves the light absorption capacity and carrier migration performance of the material, but also enhances the O2 adsorption amount and 2e-ORR selectivity, and improves the long-term stability of the material.

Benefits of technology

It has achieved significant improvement in the photocatalytic performance of the material, high catalytic activity, fast hydrogen peroxide generation rate, simple operation, low energy consumption, green and environmentally friendly, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158612B_ABST
    Figure CN119158612B_ABST
Patent Text Reader

Abstract

The present invention discloses a crystalline g-C3N4 material co-modified by doping and defects, and a preparation method and application thereof. The preparation method of the material comprises the following steps: subjecting a urea raw material to a heat treatment I to obtain a urea precursor; mixing the urea precursor with a eutectic salt containing lithium chloride and sodium chloride and subjecting the mixture to a heat treatment II under a protective atmosphere to obtain the urea precursor. The crystalline g-C3N4 material co-modified by doping and defects obtained by the present invention has good optical properties, excellent carrier separation and migration capabilities, higher O2 adsorption capacity, and efficient 2e ‑ ORR selectivity and long-term stability can be used as a photocatalyst for the efficient production of hydrogen peroxide, and has potential application value in seawater. Its preparation method is simple, low cost, and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graphite carbon nitride material, in particular to a high-yield H2O2-doped and defect-co-modified crystalline g-C3N4 material, and also to a preparation method and application thereof, belonging to the technical field of material preparation. Background Art

[0002] Since the first report of artificial photocatalytic hydrogen evolution, photocatalytic technology integrating multiple disciplines has been advancing towards the direction of efficient utilization of solar energy. It uses H2O, O2 and other substances as raw materials, uses semiconductor materials for artificial photosynthesis, and realizes the effective conversion and storage of solar energy. At present, valuable chemicals such as H2 and CH4 have been synthesized using this technology, which has greatly alleviated the current situation of energy shortage. Among them, H2O2 is a green, safe and efficient oxidant, which is widely used in wastewater treatment, pulp bleaching and pathogenic microorganism inactivation. H2O2 can also be used as a high-energy carrier for fuel cells, which is easier to store and transport. Compared with the traditional H2O2 generation process-anthraquinone method, solar-driven photocatalytic production of H2O2 is considered to be an economical and environmentally friendly synthesis method. As a photocatalytic semiconductor, graphite carbon nitride (g-C3N4) has the advantages of simple preparation, stable structure, and non-toxicity. At the same time, it can be activated under visible light and exhibits relatively excellent photocatalytic performance. However, the efficiency of H2O2 production from pristine g-C3N4 is still limited by limited visible light absorption, high recombination rate of charge carriers, poor adsorption capacity (O2), and low two-electron oxygen reduction (2e-ORR) selectivity.

[0003] Therefore, providing a carbon nitride photocatalyst with strong light absorption ability, high photogenerated carrier migration performance, good catalytic performance, and precise control is of great significance for the efficient catalytic production of H2O2. Summary of the invention

[0004] In view of the shortcomings of the prior art, the first object of the present invention is to provide a crystalline g-C3N4 material co-modified with doping and defects. The material has good optical properties, excellent carrier separation and migration capabilities, higher O2 adsorption capacity, efficient 2e - ORR selectivity and long-term stability performance.

[0005] The second object of the present invention is to provide a method for preparing a crystalline g-C3N4 material co-modified with doping and defects. The method is simple, low-cost and suitable for industrial production.

[0006] The third object of the present invention is to provide an application of a doped and defect co-modified crystalline g-C3N4 material. The material can be used as a photocatalyst for the preparation of hydrogen peroxide, has high catalytic activity, and a fast hydrogen peroxide generation rate.

[0007] In order to achieve the above technical objectives, the present invention provides a method for preparing a doped and defect co-modified crystalline g-C3N4 material, the method comprising subjecting a urea raw material to a heat treatment I to obtain a urea precursor; mixing the urea precursor with a eutectic salt comprising lithium chloride and sodium chloride and subjecting the mixture to a heat treatment II under a protective atmosphere to obtain a urea precursor; the molar ratio of the lithium chloride to the sodium chloride is 2 to 5:1.

[0008] The present invention firstly heat-treats urea to obtain a urea precursor skeleton structure, and then heat-treats the urea precursor skeleton structure with lithium chloride and sodium chloride eutectic salt under a protective atmosphere to obtain a sodium / lithium doped and defect co-modified crystalline g-C3N4 material. The g-C3N4 synthesized by the present invention using single urea as raw material has a porous thin nanostructure. During the heat treatment process, urea can be decomposed into CO2 and H2O and the like to escape, thereby promoting the formation of a porous structure. This characteristic can provide abundant reaction sites for the recrystallization reaction between the urea and the metal chloride. At the same time, a urea precursor is first synthesized and then mixed with a metal salt for heat treatment. On the one hand, the breaking of hydrogen bonds and the deamination reaction in the precursor can be accelerated, thereby promoting the formation of a highly crystalline polyheptazine imide (PHI) structure, showing an extended and fully condensed conjugated structure, accelerating the migration of carriers in the plane, and reducing the carrier recombination caused by defects, thereby enhancing the light absorption capacity and achieving a significant improvement in the photocatalytic performance. On the other hand, effective control of the crystal structure and morphological characteristics of carbon nitride can be achieved, and the use of organic solvents in the synthesis process can be avoided, which is in line with the principles of green chemistry. In addition, the dosage ratio of lithium chloride to sodium chloride determines the melting point of the eutectic salt and the properties of the reaction medium. Controlling the molar ratio of lithium chloride to sodium chloride within an appropriate range can control the reaction environment, facilitate the regulation of the synthesis process, promote the re-condensation and recrystallization of melon-based carbon nitride, and help form a highly crystalline polyheptazine imide (PHI) structure, exposing more abundant active sites. Too high or too low a molar ratio will affect the specific surface area and the number of active sites of the material, and may even cause structural damage, leading to pore collapse.

[0009] As a preferred solution, the conditions of the heat treatment I are: the atmosphere is an oxygen-containing atmosphere, the temperature is 400-550°C, and the time is 2-4h.

[0010] As a preferred solution, the oxygen-containing atmosphere is air.

[0011] As a preferred solution, the mass ratio of the urea precursor to the eutectic salt is 1:8-15.

[0012] As a preferred solution, the protective atmosphere is a nitrogen atmosphere.

[0013] As a preferred solution, the temperature of the heat treatment II is 500-600°C and the time is 3-6h.

[0014] As a preferred solution, water washing is used to remove impurities after the heat treatment II is completed. The heat-treated material is washed with boiling deionized water to remove the metal salts remaining on the surface.

[0015] The present invention also provides a doping and defect co-modified crystalline g-C3N4 material, which is prepared by the above method.

[0016] The present invention also provides an application of a doped and defect co-modified crystalline g-C3N4 material as a photocatalyst for preparing H2O2 reaction. It has high catalytic activity, fast hydrogen peroxide generation rate, good catalytic effect, and greatly improves the production efficiency of hydrogen peroxide.

[0017] As a preferred solution, the doped and defect-co-modified crystalline g-C3N4 material is used as a photocatalyst for the preparation of hydrogen peroxide in an ethanol-water solution.

[0018] As a preferred solution, the process of preparing H2O2 is: mixing an ethanol aqueous solution with a doped and defect co-modified crystalline g-C3N4 material and performing a photocatalytic reaction in an oxygen atmosphere to obtain H2O2.

[0019] The present invention uses a doped and defect-co-modified crystalline g-C3N4 as a photocatalyst, mixes it with an ethanol aqueous solution, and uses a 300W xenon lamp and an ultraviolet filter to drive the catalytic reaction in an oxygen atmosphere to efficiently produce hydrogen peroxide. The doped and defect-co-modified crystalline g-C3N4 material in the present invention is highly sensitive to visible light (λ ≥ 420 nm, 40 mW cm -2 ) driven, the photogenerated carriers are excited and separated rapidly, and the photogenerated electrons are captured and stabilized by defects and alkali metal ions, and serve as reduction sites to promote the ·O2 - and 1 O2 is generated, and the photogenerated holes quickly oxidize ethanol, releasing H + , H2O2 is produced through a two-step one-electron or one-step two-electron OPR reaction.

[0020] The specific reaction principle of photocatalytic production of hydrogen peroxide is as follows:

[0021] 2H2O + 2h + → H2O2 + 2H + (1.76 V vs NHE) (1);

[0022] O2 + e - → O2 -(-0.33 V vs NHE) (2);

[0023] O2 - + e - + 2H + → H2O2(1.44 V vs NHE) (3);

[0024] O2 + 2e - + 2H + → 1,4-endoperoxide→ H2O2 (0.68 V vs NHE) (4).

[0025] As a preferred solution, the mass content of ethanol in the ethanol aqueous solution is 8-12wt%;

[0026] As a preferred solution, the mass content of the doping and defect co-modified crystalline g-C3N4 material in the ethanol aqueous solution is 0.25g~1.0g / L.

[0027] As a preferred solution, the initial pH value of the ethanol aqueous solution is 3-12, and more preferably 5-9.

[0028] As a preferred solution, the light of the photocatalytic reaction is visible light.

[0029] As a preferred solution, the visible light is provided by a 300W xenon lamp and a 420 nm ultraviolet filter.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) Compared with traditional carbon materials, the doped and defect-modified crystalline g-C3N4 material of the present invention has good optical properties, excellent carrier separation and migration capabilities, higher O2 adsorption capacity, and efficient 2e - ORR selectivity and long-term stability;

[0032] (2) The doping and defect co-modified crystalline g-C3N4 photocatalytic material of the present invention can be used as a photocatalyst for preparing hydrogen peroxide. It can achieve efficient production of hydrogen peroxide under visible light irradiation, has high catalytic activity, strong stability, fast generation rate of hydrogen peroxide, simple operation, low energy consumption, and is green and environmentally friendly. The stable reaction in NaCl solution is expected to solve the problem of alkali metal removal. Therefore, it has potential application value in photocatalytic production of hydrogen peroxide in seawater.

[0033] (3) The material preparation method is simple, the raw materials are easily available, the operation is convenient, the cost is low, and it is suitable for industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0035] Figure 1 The scanning electron microscope images are of the g-C3N4 (CN) material (a) in Comparative Example 1 of the present invention, the sodium-doped and defect-co-modified crystalline g-C3N4 (Na-CN) material (b) in Comparative Example 2, the lithium-doped and defect-co-modified crystalline g-C3N4 (Li-CN) material (c) in Comparative Example 3, and the sodium / lithium-doped and defect-co-modified crystalline g-C3N4 (NaLi-CN) material (d) in Example 1, as well as the corresponding EDS element mapping images (ej) and transmission electron microscope images (k) of NaLi-CN.

[0036] Figure 2 It is an X-ray diffraction analysis diagram of the g-C3N4 (CN) material in Comparative Example 1 of the present invention, the sodium-doped and defect-co-modified crystalline g-C3N4 (Na-CN) material in Comparative Example 2, the lithium-doped and defect-co-modified crystalline g-C3N4 (Li-CN) material in Comparative Example 3, and the sodium / lithium-doped and defect-co-modified crystalline g-C3N4 (NaLi-CN) material in Example 1.

[0037] Figure 3 The UV-vis DSR spectra (a) and energy band (b) comparison diagram of the g-C3N4 (CN) material in Comparative Example 1 of the present invention, the sodium-doped and defect-co-modified crystalline g-C3N4 (Na-CN) material in Comparative Example 2, the lithium-doped and defect-co-modified crystalline g-C3N4 (Li-CN) material in Comparative Example 3, and the sodium / lithium-doped and defect-co-modified crystalline g-C3N4 (NaLi-CN) material in Example 1 are shown.

[0038] Figure 4 This is a comparison chart of the photocatalytic H2O2 production of g-C3N4 (CN) material, sodium-doped and defect-co-modified crystalline g-C3N4 (Na-CN) material, lithium-doped and defect-co-modified crystalline g-C3N4 (Li-CN) material, and sodium / lithium-doped and defect-co-modified crystalline g-C3N4 (NaLi-CN) material under visible light (λ≥420 nm) irradiation in Example 2 of the present invention.

[0039] Figure 5This is a graph showing the change in H2O2 production from the photocatalytic reaction of sodium / lithium doped and defect co-modified crystalline g-C3N4 (NaLi-CN) under a single environmental variable in Example 3 of the present invention.

[0040] Figure 6 3. The effect of different pH values ​​on the photocatalytic H2O2 generation rate of sodium / lithium doped and defect co-modified crystalline g-C3N4 (NaLi-CN) in Example 4 of the present invention. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.

[0042] The raw materials and instruments used in the following examples are all commercially available. In the examples of the present invention, unless otherwise specified, the data obtained are the average values ​​of more than three repeated experiments.

[0043] Example 1

[0044] A method for preparing a doping and defect co-modified crystalline g-C3N4 material of the present invention specifically comprises the following steps:

[0045] (1) Place 15 g of urea as raw material in a covered crucible and heat at 5°C min in an air atmosphere. -1 The mixture was heated to 550° C. at a rate of 1000 ℃ and then maintained at the temperature for 2 hours to obtain incompletely polymerized guaryl carbon nitride.

[0046] (2) 0.6 g of melon-based carbon nitride was uniformly mixed with 6 g of LiCl and NaCl metal eutectic salt (where LiCl / NaCl = 72 / 28 mol%) and heated at 5 °C min under a nitrogen atmosphere. -1 The temperature was raised to 550°C at a rate of 1000 °C and then maintained at this temperature for calcination for 4 hours. After cooling, the residual metal salt on the surface was washed with boiling deionized water and then vacuum dried at 60°C for 12 hours to obtain Na / Li-doped and defect-co-modified crystalline g-C3N4 material, which was denoted as NaLi-CN.

[0047] Comparative Example 1

[0048] 15 g of urea was placed in a covered crucible and heated at 5 °C min under air atmosphere. -1 The mixture was heated to 550°C at a rate of 1000 °C and then kept at this temperature for 4 hours to obtain a pale yellow block of carbon nitride, which was then ground to obtain a carbon nitride material, recorded as CN.

[0049] Comparative Example 2

[0050] The carbon nitride material is prepared by the method of Example 1, except that the metal molten salt contains only NaCl, and a sodium-doped and defect-co-modified crystalline g-C3N4 material is obtained, which is recorded as Na-CN.

[0051] Comparative Example 3

[0052] The carbon nitride material is prepared by the method of Example 1, except that the metal molten salt contains only LiCl, and a lithium-doped and defect-co-modified crystalline g-C3N4 material is obtained, which is recorded as Li-CN.

[0053] The carbon nitride material (CN), sodium-doped and defect-modified crystalline g-C3N4 material (Na-CN), lithium-doped and defect-modified crystalline g-C3N4 material (Li-CN), and Na / Li-doped and defect-modified crystalline g-C3N4 material (NaLi-CN) prepared in Comparative Examples 1 to 3 and Example 1 were observed by scanning electron microscopy. The results are shown in FIG. Figure 1 .like Figure 1 As shown in (a), due to the large amount of gas released by urea during the calcination process, CN presents a block structure with abundant pores; Figure 1 (b, c) show that a single high melting point metal salt destroys the structure of CN, causing the pores to collapse and the mesoporous structure to be destroyed, so that the surface pores of Na-CN and Li-CN are significantly reduced; while the carbon nitride material NaLi-CN prepared by the present invention using lithium chloride and sodium chloride eutectic salt, such as Figure 1 As shown in (d), it presents a porous structure with a relatively smooth surface and still has abundant pores.

[0054] The Na / Li doped and defect co-modified crystalline g-C3N4 material (NaLi-CN) prepared in Example 1 of the present invention was subjected to energy dispersive x-ray spectroscopy (EDS) analysis, and the results are as follows: Figure 1 As shown in (ej), in addition to the inherent C, N, and O elements, the Na signal was clearly detected in the structure of NaLi-CN, confirming the introduction and uniform distribution of the Na element, but basically no Cl signal was detected, indicating that the Na in the sample was doped in CN in an ionic state; the high-resolution transmission electron microscopy observation results are shown in Figure 1 As shown in (k), NaLi-CN shows a clear lattice structure with lattice fringes, and the corresponding 0.47 nm lattice fringes are caused by the in-plane periodicity, confirming the formation of the crystalline NaLi-CN sample.

[0055] The carbon nitride material (CN), sodium-doped and defect-modified crystalline g-C3N4 material (Na-CN), lithium-doped and defect-modified crystalline g-C3N4 material (Li-CN), and Na / Li-doped and defect-modified crystalline g-C3N4 material (NaLi-CN) prepared in Comparative Examples 1 to 3 and Example 1 were subjected to X-ray diffraction analysis. The results are shown in Figure 2 .from Figure 2 It can be seen that CN has two characteristic diffraction peaks at 13.0 and 27.6°, corresponding to the in-plane filling motif (100) and the layer stacking distance (002) of the aromatic system, respectively; the (100) peak of Na-CN disappears, indicating that its regular tri-s-triazine ring structure is damaged, while the (002) peak becomes weaker and wider, indicating that CN is severely damaged after treatment with high-melting-point NaCl metal salt; the (100) peak of Li-CN shifts, indicating that the in-plane filling distance is expanded; in addition to shifting the (100) peak of CN to 8.5° and 9.0°, the (002) peak of NaLi-CN also shifts, indicating that the interlayer distance is reduced, which means faster interlayer charge transfer. In addition, NaLi-CN has obvious diffraction peaks at 14.8°, 22.5° and 36.6°, indicating that the ordered PHI structure is successfully regulated, resulting in high crystallinity.

[0056] The carbon nitride material (CN), sodium-doped and defect-modified crystalline g-C3N4 material (Na-CN), lithium-doped and defect-modified crystalline g-C3N4 material (Li-CN), and Na / Li-doped and defect-modified crystalline g-C3N4 material (NaLi-CN) prepared in Comparative Examples 1 to 3 and Example 1 were subjected to UV-vis DSR spectral analysis. The results are shown in Figure 3 .in, Figure 3 (a) shows that CN exhibits poor light response between 500-800 nm, and the adsorption edge is around 458 nm; NaLi-CN, Na-CN and Li-CN show red-shifted intrinsic absorption bands, among which NaLi-CN is the most obvious, indicating that NaLi-CN has the strongest In addition, defects provide abundant intermediate energy levels, so that electrons in the n orbital are excited to orbit, successfully enhancing the light absorption of carbon nitride. Based on the DSR data, the intrinsic optical band gap energy (Eg) of the above materials was determined. The results are as follows Figure 3 (b) shows that the band gaps of NaLi-CN, Na-CN and Li-CN decrease from 2.69 eV of CN to 2.57, 2.58 and 2.60 eV, respectively, indicating that the modified materials are more easily activated under light. Finally, NaLi-CN exhibits the strongest light absorption ability and the narrowest band gap, indicating that it has good photoresponse characteristics.

[0057] Example 2

[0058] This embodiment is a method for preparing hydrogen peroxide by using the doped and defect co-modified crystalline g-C3N4 material (NaLi-CN) prepared by the present invention as a photocatalyst. Specifically, the doped and defect co-modified crystalline g-C3N4 prepared in Example 1 of the present invention is used to catalyze the generation of hydrogen peroxide under visible light irradiation and in an ethanol solution system, comprising the following steps:

[0059] Take a 1L ethanol aqueous solution with a mass fraction of 10%, add 0.5g of sodium / lithium doped and defect co-modified crystalline g-C3N4 material (NaLi-CN), and after the suspension O2 reaches saturation, use a 300W xenon lamp and a 420 nm UV filter as the light source to carry out photocatalytic experiments.

[0060] Control group 1: Take 1L of 10% ethanol aqueous solution, add 0.5g CN material, and after the suspension reaches saturation with O2, use a 300W xenon lamp and a 420 nm UV filter as the light source to carry out a photocatalytic experiment.

[0061] Control group 2: Take 1L of 10% ethanol aqueous solution, add 0.5g Na-CN material, and after the suspension reaches saturation with O2, use a 300W xenon lamp and a 420 nm UV filter as the light source to carry out a photocatalytic experiment.

[0062] Control group three: Take 1L of ethanol aqueous solution with a mass fraction of 10%, add 0.5g of Li-CN material, and after the suspension O2 reaches saturation, use a 300W xenon lamp and a 420 nm ultraviolet filter as the light source to carry out photocatalytic experiments.

[0063] The start of illumination was recorded as time 0. Samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min after the reaction. The H2O2 content was determined by iodine titration. The measurement results are shown in Figure 4 .from Figure 4 As can be seen from the figure, CN exhibits a moderate level of H2O2 production rate (about 0.23 mmol g -1 h -1 ), the H2O2 production rates of Na-CN and Li-CN were 9.96 mmol g -1 h -1 and 9.20 mmol g -1 h -1 , which are 44 and 40 times that of CN; and the rate of generating H2O2 from NaLi-CN prepared by the present invention reaches 25.65 mmol g-1 h -1 , which is 113 times that of CN. The results show that the introduction of composite alkali metals and defects through the eutectic salt method can significantly improve the photocatalytic performance of the material and increase the production rate of hydrogen peroxide.

[0064] Example 3

[0065] This example is about the effect of adding sacrificial agent ethanol, dissolved oxygen, catalyst and light source on the efficiency of hydrogen peroxide generation, and specifically includes the following steps:

[0066] Take 0.5g of sodium / lithium doped and defect co-modified crystalline g-C3N4 (NaLi-CN) material and place it in 1L of 10% ethanol aqueous solution. After the suspension O2 reaches saturation, a photocatalytic experiment is carried out using a 300W xenon lamp and a 420 nm ultraviolet filter as light sources.

[0067] Control group 1: Take 0.5g of sodium / lithium doped and defect co-modified crystalline g-C3N4 (NaLi-CN) material and place it in 1L of ultrapure water. After the suspension O2 reaches saturation, use a 300W xenon lamp and a 420 nm UV filter as the light source to carry out a photocatalytic experiment.

[0068] Control group 2: Take 0.5g of sodium / lithium doped and defect co-modified crystalline g-C3N4 (NaLi-CN) material, place it in 1L of 10% ethanol aqueous solution, use a 300W xenon lamp and a 420 nm ultraviolet filter as the light source, and carry out photocatalytic experiments.

[0069] Control group three: Take 0.5g of sodium / lithium doped and defect co-modified crystalline g-C3N4 (NaLi-CN) material and place it in 1L of 10% ethanol aqueous solution. After the suspension N2 reaches saturation, use a 300W xenon lamp and a 420 nm UV filter as the light source to carry out photocatalytic experiments.

[0070] Control group 4: Take 1L of 10% ethanol aqueous solution, after O2 reaches saturation, use 300W xenon lamp and 420 nm UV filter as light source to carry out photocatalytic experiment.

[0071] Control group five: Take 0.5g of sodium / lithium doped and defect co-modified crystalline g-C3N4 (NaLi-CN) material, place it in 1L of 10% ethanol aqueous solution, and carry out catalytic experiments in the dark.

[0072] Samples were taken from the reaction system at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min of catalytic reaction, and the H2O2 content was determined by iodine titration. The test results are as follows: Figure 5As shown: In the dark (control 5) or without adding NaLi-CN (control 4), H2O2 is basically not produced; in the system without ethanol (sacrificial agent) (control 1), NaLi-CN has the ability to stably generate H2O2, but the generation rate is greatly reduced; when the atmosphere of the system becomes air (control 2), the production of H2O2 drops sharply, and when it becomes N2 (control 3), the production of H2O2 is basically suppressed. It can be seen that sacrificial agent ethanol and dissolved oxygen are important factors for the stable and efficient production of H2O2 by photocatalysis.

[0073] Example 4

[0074] This example shows the effect of different initial pH conditions on the photocatalytic H2O2 production effect. The sodium / lithium doped and defect co-modified crystalline g-C3N4 material prepared in Example 1 is used as a photocatalyst, and specifically includes the following steps:

[0075] Take 6 portions of 1L ethanol aqueous solution with a mass fraction of 10%, add 0.5g of sodium / lithium doped and defect co-modified crystalline g-C3N4 material (NaLi-CN), adjust the initial pH value of the resulting suspension to 3, 5, 5.63, 7, 9, and 12, and after O2 reaches saturation, use a 300W xenon lamp and a 420 nm UV filter as the light source to carry out photocatalytic experiments.

[0076] The start of illumination was recorded as time 0. Samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min after the reaction. The H2O2 content was determined by iodine titration. The measurement results are shown in the figure. Figure 6 As shown in the figure, NaLi-CN can stably generate H2O2 in a wide pH range (3-12), and is more efficient in the pH range of 5-9. The most favorable pH for the generation of H2O2 is 5.63, with a generation amount of 25.65 mmol g -1 h -1 ; When the pH value decreases from 5 to 3, the generation rate of H2O2 slows down relatively, indicating that the sodium / lithium doped and defect co-modified crystalline g-C3N4 (NaLi-CN) material has strong environmental tolerance.

[0077] Depend on Figure 4 , Figure 5 , Figure 6 It can be seen that the sodium / lithium doped and defect co-modified crystalline g-C3N4 (NaLi-CN) material prepared in the present invention has a good ability to produce H2O2 by photocatalysis. Under the conditions of NaLi-CN catalyst concentration of 0.5 g / L, 10% ethanol as sacrificial agent, initial pH of suspension of 5.63, O2 saturated atmosphere and visible light, the H2O2 yield of the present invention can reach 25.65 mmol g-1 h -1 , which is 113 times that of ordinary CN materials. Therefore, the method of photocatalytically producing H2O2 by using the crystalline g-C3N4 material co-modified with doping and defects in the present invention realizes the efficient production of hydrogen peroxide under visible light irradiation, and has the advantages of high catalytic activity, fast generation rate, simple operation, low energy consumption, green environmental protection, etc. At the same time, it has long-term stability and is expected to solve the problem of alkali metal removal in NaCl solution.

[0078] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a crystalline g-C3N4 material co-modified by doping and defects, characterized in that: The urea raw material is subjected to heat treatment I to obtain a urea precursor; the urea precursor is mixed with a eutectic salt containing lithium chloride and sodium chloride and subjected to heat treatment II under a protective atmosphere to obtain; the molar ratio of lithium chloride to sodium chloride is 2-5:1; The conditions of the heat treatment I are: an oxygen-containing atmosphere, a temperature of 400-550° C., and a time of 2-4 h; The temperature of the heat treatment II is 500-600°C and the time is 3-6h.

2. The method for preparing a doping and defect co-modified crystalline g-C3N4 material according to claim 1, characterized in that: The mass ratio of the urea precursor to the eutectic salt is 1:8-15.

3. The method for preparing a doping and defect co-modified crystalline g-C3N4 material according to claim 1, characterized in that: The protective atmosphere is a nitrogen atmosphere.

4. A crystalline g-C3N4 material co-modified by doping and defects, characterized in that: The method is prepared by any one of claims 1 to 3.

5. An application of a doping and defect co-modified crystalline g-C3N4 material as claimed in claim 4, characterized in that: As a photocatalyst for the preparation of H2O2.

6. The use of a doping and defect co-modified crystalline g-C3N4 material according to claim 5, characterized in that: The process of preparing H2O2 reaction is: mixing ethanol aqueous solution with doping and defect co-modified crystalline g-C3N4 material and performing photocatalytic reaction in oxygen atmosphere to obtain H2O2.

7. The use of a doping and defect co-modified crystalline g-C3N4 material according to claim 6, characterized in that: The mass content of ethanol in the ethanol aqueous solution is 8-12wt%; The mass content of the doping and defect co-modified crystalline g-C3N4 material in ethanol aqueous solution is 0.25g~1.0g / L.

8. The use of a doping and defect co-modified crystalline g-C3N4 material according to claim 6 or 7, characterized in that: The light of the photocatalytic reaction is visible light.